An Economic and Analytical Study to Estimate the Water Footprint and Virtual Water Trade for Grain Crops in Iraq (NTU Journal of Agriculture and Veterinary Science, 2024)
Iraq is one of the most countries in the region and the world that may face a major challenge in front of its water resources, represented by the Tigris and Euphrates rivers, which are the largest rivers and sources of water due to the policies of the countries sharing with it and the upstream countries due to the construction of water dams on it, the latest of which is the Turkish Ilisu Dam on the Tigris River, which caused a decrease in the rate of A decrease of (-1.2%),  The objective of the research is to examine the reality of water footprint indicators and standards and the virtual water trade of grain crops for the period (2003-2021).The results of the research during the study period indicated a decrease in water quantities from (57.38) billion m3 cubic meters in (2003) to (22.95) billion m3 cubic meters in (2021), The average external, internal and college water footprint of the wheat crop was (6.98, 15.18 and 22.18) billion m3, respectively, The average external, internal and total water footprint of the rice crop was (7.49, 4.21 and 13.68) billion m3, respectively, While the average quantity of virtual water imported for wheat crop (6.99) billion m3, the average quantity of virtual water imported for rice crop reached (9.39) billion m3, Researchers recommended that attention be paid to Iraq's water policy and that alternatives be found to avoid the shortage of water contained therein by focusing on the obligation of farmers to water metering, supplementary irrigation, identifying current and future water needs and conducting a comprehensive water supply survey.